2018
DOI: 10.3892/br.2018.1076
|View full text |Cite
|
Sign up to set email alerts
|

Oral lactoferrin influences psychological stress in humans: A single‑dose administration crossover study

Abstract: Lactoferrin is a secretory protein with various physiological functions. Bovine lactoferrin has been demonstrated to alleviate psychological stresses in rats, but this effect in humans has not yet been assessed. The present study aimed to investigate the changes in psychological stress markers following a calculation task, with either lactoferrin or a placebo orally administered prior to the task. A total of 16 healthy female college students visited Juntendo University, Inzai, Japan following an overnight fas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 35 publications
(41 reference statements)
0
15
0
Order By: Relevance
“…Maekawa et al (2017) reported that the lactoferrin ameliorates corticosterone-related acute stress and hyperglycemia in rats, and its effect, which could be attributed to the activation of the HPA axis. In a recent report performed in human, Shinjo et al (2018) indicated the possible application of lactoferrin in managing psychological stress being able to exert a suppression effect on the changed in parasympathetic and sympathetic activities evoked by the calculation task. Therefore, the pathway of actuation in stress response it could be at both levels (HPA and autonomic nervous system (SNA)).…”
Section: Discussionmentioning
confidence: 99%
“…Maekawa et al (2017) reported that the lactoferrin ameliorates corticosterone-related acute stress and hyperglycemia in rats, and its effect, which could be attributed to the activation of the HPA axis. In a recent report performed in human, Shinjo et al (2018) indicated the possible application of lactoferrin in managing psychological stress being able to exert a suppression effect on the changed in parasympathetic and sympathetic activities evoked by the calculation task. Therefore, the pathway of actuation in stress response it could be at both levels (HPA and autonomic nervous system (SNA)).…”
Section: Discussionmentioning
confidence: 99%
“…Stress-protective effects of lactoferrin administration before stress are known, in particular, the severity of inflammation decreases with subsequent exposure to stress. (20) However, the presence of marginal high basic values of salivary lactoferrin may reflect a pronounced activity of oxidative processes during the development of inflammation in the tissues, which does not allow an adequate vascular and immune response to develop with subsequent exposure to cold and to ensure the preservation of body temperature. Therefore, the focus of vegetative and immune reactions in individuals with a high baseline lactoferrin level (more than 75th percentile)in terms of adaptation and/or maladaptation at low temperatures needs further special study.…”
Section: Discussionmentioning
confidence: 99%
“…Although no such analysis has been published before, experimental studies in rodents and humans suggest a possible physiological base for this association. Single-dose oral administration of bovine LF was found to mitigate the physiological response to experimentally induced psychological stress in rats [60] and humans [61]. Thus, it is possible that in breastfeeding mothers with increased anxiety, LF is preferentially used to alleviate the consequences of higher stress and LF transfer to milk remains low.…”
Section: 1)mentioning
confidence: 99%